2019
DOI: 10.24925/turjaf.v7i3.384-389.2301
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Sıcaklık ve Sürelerde Ön Kurutma İşlemine Tabi Tutulduktan Sonra Kızartılmış Glütensiz Cipslerin Yağ Absorplama Kapasitelerinin ve Bazı Fizikokimyasal İçerikleri ile Duyusal Özelliklerinin Belirlenmesi

Abstract: The aim of this study was to investigate the moisture and oil uptake capacities of gluten-free chips by pre-drying at different temperatures and times before deep frying. In addition, the determination of some physicochemical contents and sensory properties of the chips were another goal in this study. As a result of pre-drying up to 60°C and 15 min, the dry matter content of the samples increased while the temperature decreased to 70° C. Similarly, the oil content of the samples decreased until the same tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…It was reported that the moisture content and water activity values of crispy fat-free chips produced from sweet potato dried by microwave vacuum drying method were 2.7 ± 0.6% (wet basis) and 0.262, respectively [14]. Similar values, between 0.88% and 5.45% of moisture content were reported by Yüksel et al [15]. The MC (2.59-3.06%) and a w (0.185-0.192) values of breadsticks with 5 and 10% red grape pomace reported by Rainero et al [16] were compatible with our results.…”
Section: Changes In Proximate Compositionsupporting
confidence: 75%
“…It was reported that the moisture content and water activity values of crispy fat-free chips produced from sweet potato dried by microwave vacuum drying method were 2.7 ± 0.6% (wet basis) and 0.262, respectively [14]. Similar values, between 0.88% and 5.45% of moisture content were reported by Yüksel et al [15]. The MC (2.59-3.06%) and a w (0.185-0.192) values of breadsticks with 5 and 10% red grape pomace reported by Rainero et al [16] were compatible with our results.…”
Section: Changes In Proximate Compositionsupporting
confidence: 75%